Optimasi Formula Tablet Lepas Lambat Tramadol HCl dengan Kombinasi Matriks Mukoadhesif PVP dan Xanthan Gum secara Simplex Lattice Design - Chaesti Setyo Hastuti; Ilham Kuncahyo; Muhammad Dzakwan (Jurnal Farmasi Indonesia, 2014)
Tramadol HCl is a synthetic opioid of cyclohexanol group which acts as an analgesic. To improve the comfort and compliance of patient, therefore tramadol HCl is made in sustained release tablet. In this study, sustained release tablet of tramadol HCl was combined with PVP and xanthan gum mucoadhesive matrix. This study was made in four formulas, they were: control formula (without the matrix), F I (25% PVP : 75% xanthan gum), F II (50% PVP : 50% xanthan gum), and F III (75% PVP : 25% xanthan gum). The tablets were made by dry granulation and compressed to 250 mg weight of tablet. The obtained granules and tablets were tested for the physical properties. The properties determination of the optimum formula used Simplex Lattice Design method (SLD) with Software Design Expert 8.0.6. The parameters used were: flowing time, hardness, friability, and disolution. The experimental results and the theoretical optimum formula were analyzed using t-test. The optimum formula sustained release tablet of tramadol HCl with PVP and xanthan gum mucoadhesive matrix combination by Simplex Lattice Design was obtained in proportion of 55,031% PVP and 44,969% xanthan gum. Pattern of tramadol HCl release on the optimum formula followed diffusion mechanism and zerro orde kinetic. The response of physical properties of optimum formula was obtained from prediction result and examination showed that there was not different significant.